Suriname: an overview - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
First, the document includes geographical, historical and political data above Suriname. Continuously, section two refers to the economy: an overview; section three to the population and employment; section four to the exchange rate; section five to the exports and imports (bauxite, rice exports and shrimps exports, among other items). Then, section six to the rural poverty; section seven to the agricultural production (with respect to land use and water management; three agricultural production systems can be distinguished: a) irrigated crop production; b) rainfed crop production; c) food plots). Section eight to the liverstock production; section nine to the government organization; and, finally, section ten to the international financing and technical assistance.